2020
DOI: 10.1016/j.jalz.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Leisure activity and social integration mitigate the risk of dementia related to cardiometabolic diseases: A population‐based longitudinal study

Abstract: Introduction:The effect of comorbid cardiometabolic diseases (CMDs), including diabetes, heart diseases, and stroke, on dementia remains unclear. Methods:A cohort of 2648 dementia-free adults aged ≥60 years was followed up for 12 years. An active lifestyle was defined in accordance with the engagement in leisure activities and/or a social network. Cox models were used in data analysis. Results:The multiadjusted hazard ratio (HR, 95% confidence interval) of dementia was 1.41 (1.07-1.86) for one, 2.38 (1.58-3.59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…Indeed, we found that comorbid diabetes and heart disease doubled the risk of both CIND and its progression to dementia, whereas neither diabetes nor heart disease alone conferred a significant risk of either outcome. This is in line with our previous work demonstrating that comorbid cardiometabolic diseases impact dementia risk in a dose‐dependent manner 46 . This finding also reinforces the point that it is not diabetes per se but rather its severity (in terms of glycemia and the burden of complications like heart disease) that is related to cognitive deterioration.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we found that comorbid diabetes and heart disease doubled the risk of both CIND and its progression to dementia, whereas neither diabetes nor heart disease alone conferred a significant risk of either outcome. This is in line with our previous work demonstrating that comorbid cardiometabolic diseases impact dementia risk in a dose‐dependent manner 46 . This finding also reinforces the point that it is not diabetes per se but rather its severity (in terms of glycemia and the burden of complications like heart disease) that is related to cognitive deterioration.…”
Section: Discussionsupporting
confidence: 92%
“…Additional studies suggest that remaining socially and mentally active throughout life may support brain health and possibly reduce the risk of Alzheimer's and other dementias 121,160–172 . Socially and cognitively stimulating activity might help build cognitive reserve.…”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…These three possibly modifiable risk factors can cause an accumulation of neurotoxic peptides and oxidative stress level changes in the brain that in time may result in cognitive impairment and dementia [ 78 , 81 , 89 ]. Similarly, the higher risk of dementia in the elderly individuals with various comorbid cardiometabolic diseases such as diabetes mellitus or stroke can be moderated by social engagement and physical activities [ 131 ]. The effects of (non-)modifiable risk and protective factors are also age- and gender-dependent.…”
Section: Future Possible Research Directions and Trends In The Trementioning
confidence: 99%